Internalisasi Nilai-Nilai Pendidikan Agama Islam Dalam Mata Pelajaran PJOK Di Madrasah Ibtidaiyah Al Mujahidin Kedu - Al Hakim, Muhammad Fadloli (Institut Islam Nahdlatul Ulama Temanggung, 2021)
ABSTRACT Education in Indonesia in the last decade has reaped many problems, one of which is the decay of the morals of the younger generation and this is an important discussion that deserves our attention. The essence of the purpose of Islamic Religious Education in general is to form students so that they become problems, so there needs to be a breakthrough, one of which is starting the internalization of Islamic religious education values ​​in PJOK subjects in the classroom and outside the classroom, especially PJOK subjects. This study uses a descriptive qualitative approach. The results showed that (1) the process of internalizing the values ​​of Islamic religious education in PJOK subjects at MI Al Mujahidin was carried out in several stages: a) the value transformation stage, b) the value transaction stage, c) the transliteration stage. In this transliteration stage there is a need stage, namely the stage where students will feel the need if it is not carried out and the evaluation stage is to see how far the values ​​of Islamic religious education are carried out in their daily lives. (2) Internalized Islamic religious education values ​​are aqidah, morals, fiqh (3) The results of internalizing Islamic religious education values ​​in PJOK subjects at MI Al Mujahidin are the formation of students who are physically and mentally healthy and have personal religious ones. In the internalization of PAI values, there are three aspects, namely physical aspects, spiritual aspects, and spiritual aspects. The three of them are mutually sustainable in order to form students who are physically and mentally healthy and have good morals. Keywords: Internalization, Islamic Religious Education Values, PJOK Lessons